The stay of humoral immunity in bacterial dysbiosis and bacterial vaginosis - Hruzevskyi, O; Minukhin, V (Annals of Mechnikov's Institute, 2020)
Introduction. The state of dysbiosis and bacterial vaginosis (BV) is characterized by the formation of both systemic and local immune deficiency, which corresponds to the increase in the number of pathogenic microbiota. An important reason of bacterial vaginosis’ development is local immunodeficiency corresponding with decreasing of colonization resistance of vaginal fluid. This phenomenon develops due to disturbance of normal vaginal microbiocenosis, secretion of antimicrobial substances and provision of normal immune defense. Recognition of the role and mechanisms of local immunodeficiency’s development can be very important scientific achievement in the field of microbiology, immunology and pathology of human vaginal microflora. However, nowadays ratio of systemic and local immune reactions in bacterial vaginosis isn’t revealed completely. Thus, the aim of the investigation was to determine the stay of humoral immunity according to the content of immunoglobulins (Ig) in the blood and vaginal fluid in different degrees of bacterial dysbiosis and BV. Material and methods. Data from 298 women were divided into groups according to index of pathogenic microbiota condition (IPMC) and the pathogenic microbiota indicator (PMI): normocenosis (n=53), dysbiosis I (n=128) and II degree (n=117), among the last allocated 83 patients with PMI>1 lg gE/sample, where was drawn diagnosis “Bacterial Vaginosis”. The criterion of exclusion there was presence of pathogenic microorganisms in vaginal epithelium scrapings. These representatives were: Trichomonas vaginalis, Neisseria gonorrhoeae, Chlamydia trachomatis та Herpes Simplex Virus 1,2. Presence of leucocytes more than 15-20 cells in the field of vision in vaginal smears indicated inflammatory reaction also was the criterion of exclusion. Molecular genetic studies of posterolateral wall of the vagina epithelium scrapings was performed by Real-time polymerase chain reaction. A content of facultative and obligate anaerobic bacteria, myco- and ureaplasma, yeast-like fungi was studied quantitatively. With the help of Enzyme-Linked Immunoassay (ELISA) contents of IgA, IgM, IgG, IgG2, secretory IgA (sIgA) were determined in blood and vaginal fluid. Spectrophotometry was used for quantitative evaluation of circulating immune complexes (CIC) contents in the blood and immune complexes in vaginal fluid (ICVF). For descriptive statistics of data there were used arithmetical mean (М) and average error (mistake). Paired independent data samplings were compared according to Mann-Whitney U-test (U). Significance of all differences accepted when p<0,05. For statistic and regressive analyses package of software “Statistica 10” (StatSoft, Inc., USA) was applied. Results and discussion. While development of bacterial dysbiosis and BV there was observed progressive increasing of CD22 lymphocytosis, contents of IgM, IgG і IgG2. In our investigations quantity of CD22+ lymphocytes was constantly larger in manifested dysbiosis in comparison with normocenosis. Maximal content of CD22+ lymphocytes was noted in BV. Contents of IgA, sIgA and CIC had tendency to decreasing. In general, it’s possible to conclude that blood CIC level decreases according to the progressing of dysbiosis. Hence, its more level in 2 subgroup of 2 group and in 1 subgroup of 3 could indicate reactive changes in immune system. Content of ICVF in I degree dysbiosis in comparison with normocenosis was not change significally. Simultaneously, in I degree dysbiosis and in 1-st subgroup of II degree dysbiosis this inex was significally more. In BV content of ICVF was twice less than in normocenosis. These phenomena were synchronous with blood CIC levels, and reflected sharp parallel decreasing of CIC formation both in the bloodstream and in vaginal fluid during BV. Local immunodeficiency with immunoglobulins’ (especially, IgA and sIgA) and ICVF levels decreasing progressed while development of bacterial dysbiosis and BV also. Therefore, the stay of systemic humoral immunity in BV didn’t correlate always with such one in vaginal fluid. Conclusion. Systemic humoral immunity while development of BV was changed, but it wasn’t reflected completely the stay of defences in vaginal fluid. In general, there was present dissonance of these two systems’ reaction: activation of systemic level and suppression on local level. DOI: 10.5281/zenodo.3885147